The 1971 Election in Semarang City: Golkar’s Curated Contestation in Newspaper - Putri, Lamia Rozianna; Putri Agus Wijayati (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2025)
This research is a study of Golkar news curated in newspapers during the 1971 election. The writing uses historical research methods consisting of heuristics, verification, interpretation, and historiography stages. As a result, Golkar, to win the campaign, used the ABG (ABRI, Bureaucracy, Golkar) strategy. Newspaper reports revealed the strategy's implementation through a variety of tactics, including songs, rhymes, and slogans. Golkar used these methods to convey his presence among the people. The news also narrated how much the people supported Golkar. Furthermore, one can observe the disparities in coverage between government-affiliated and independent newspapers. In the end, the propaganda through these newspapers succeeded in making Golkar win the election contest in Semarang City with 58% of the vote. After the victory, the government established KORPRI and conducted party diffusion.